Analisis Aspek Hukum dan Manajemen Kontrak Dalam Industri Konstruksi - Simanjuntak, Manlian Ronald Adventus (LAW REVIEW, 2002)
In life cycle construction industry, each phase of the activities must be managed by the law, such as a contract. All participants who join in construction industry, such as owner, architect, civil engineering, suppliers in each phase of life cycle construction do their professional ethics with responsibility.. Contract in construction industry will not only manage all the participants in constructrion, but also will treat the risks of construction. Â In contract management, there are key activities that must be done, viz: preparing and making the contract, contract as a guidance of work (TOR), contract as acontrolling, administration of the contract. In this paper it will be analyzed the law aspect and contract management in construction industry systematically in order to keep all the activities in life cyle construction doing well.Â